2019
DOI: 10.1002/ird.2386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for Irrigation Water Purposes of Groundwater Quality in the Vicinity of Sivas City Centre (Turkey) by Using Gis and an Irrigation Water Quality Index

Abstract: In this study, the physical and chemical characteristics of wet and dry season groundwater quality parameters of 35 wells within the provincial boundaries of Sivas were used for calculations such as sodium adsorption ratio (SAR), Kelly's ratio (KR), sodium percentage (Na%), permeability index (PI), residual sodium carbonate (RSC) and magnesium hazard (MH), which are used in irrigation water quality ratings. Also, the irrigation water quality index (IWQI) was calculated for all groundwater sources within the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Many types of research have indicated that except for geological origin, vast pollution in groundwater resources is because of the inappropriate disposal of solid waste, sewage and overuse of agrochemical products (Aleem et al, 2018). Karakuş and Yildiz (2019) and Kiy and Arslan (2021) investigated groundwater quality for irrigation and drinking purposes in Turkey using water quality indices. Alamdar et al (2019) and Badeenezhad et al (2020) stated that the groundwater hydrochemistry in the Shiraz plain (south of Iran) is in the main the result of human activity, but is influenced to some degree by natural processes.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of research have indicated that except for geological origin, vast pollution in groundwater resources is because of the inappropriate disposal of solid waste, sewage and overuse of agrochemical products (Aleem et al, 2018). Karakuş and Yildiz (2019) and Kiy and Arslan (2021) investigated groundwater quality for irrigation and drinking purposes in Turkey using water quality indices. Alamdar et al (2019) and Badeenezhad et al (2020) stated that the groundwater hydrochemistry in the Shiraz plain (south of Iran) is in the main the result of human activity, but is influenced to some degree by natural processes.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the KR values ranged between 0,23 and 2 ( Figure 4 e). According to Karakus and Yidiz (2020) , the KR values lower than 1 indicates that water is suitable for irrigation and values higher than 1 indicate that water is unsuitable for irrigation purposes. Figure 4 e shows that all groundwater samples are suitable for irrigation purposes except for sites 7 and 17.…”
Section: Resultsmentioning
confidence: 99%
“…The applicability of the procedure is possible due to the natural water having anions and cations in chemical equilibrium. According to studies reported in the literature, the dominant cations in water proved to be Na + , Mg 2+ , and Ca 2+ , while SO 4 2− , Cl − , and HCO 3 − were the most abundant anions [33][34][35][36]. The concentration of chemical components in natural groundwater depends on many processes and conditions, including the availability and solubility of minerals, the geochemical environment (pH and EC), and exchange processes, which may be different for the type of aquifer water.…”
Section: Piper and Gibbs Diagrammentioning
confidence: 99%